Luxury values and experience as drivers for consumers to recommend and pay more - Loureiro, S. M. C. (2014)
The study aims to analyse how individual and social luxury values affect the customers' attitude, behavioural control and subjective norms and how these variables and past experience influence the intentions to recommend and pay more for luxury clothing in the Brazilian market. Respondents were surveyed in the São Paulo area of Brazil through a panel sample and using an online survey during April and May 2012. The findings suggest that individual values influence intentions positively. Social values have a positive influence on subjective norms and a negative influence on behavioural control. Past experience does not influence intentions significantly. Extend the theory of planned behaviour introducing luxury values as external variables and past experience as a direct antecedent of intentions to pay more and to recommend the luxury brand.